Optimalisasi Penggunaan Efek Visual Oleh Editor Untuk Memperjelas Narasi Dalam Video Promosi Prodi Ilmu Komunikasi - Muhammad Farhan Wicaksana; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This final project discusses the optimization of the use of visual effects in the promotional video of the Dharma Andalas University Communication Studies Program to clarify the narrative conveyed. Along with the development of technology and digital media, short videos have become an effective communication tool in conveying information to audiences in a fast and interesting way. Visual effects have an important role in increasing visual appeal, clarifying messages, and strengthening the identity of the study program in an effort to attract prospective students. This final project uses an audiovisual production method that includes three main stages, namely pre-production, production, and post-production. In the pre-production stage, concept planning, script drafting, and storyboarding were carried out. The production stage involves shooting in accordance with the visual needs that have been designed. Meanwhile, in the post-production stage, the editing process is carried out by applying various visual effects techniques, such as transitions, motion graphics, and color grading to improve visual quality and support the delivery of a clearer and more interesting narrative. The final project show that the optimal application of visual effects can increase the audience's understanding of the message conveyed in promotional videos. In addition, the use of appropriate editing techniques also contributes to creating a more interactive and informative video. Thus, this research is expected to be a reference in the development of visual communication strategies, especially in the field of education promotion through digital media.